2016
DOI: 10.1007/s11999-016-4726-2
|View full text |Cite
|
Sign up to set email alerts
|

The Alpha-defensin Test for Periprosthetic Joint Infections Is Not Affected by Prior Antibiotic Administration

Abstract: BackgroundPrevious studies have demonstrated that the administration of antibiotics to patients before performing diagnostic testing for periprosthetic joint infection (PJI) can interfere with the accuracy of test results. Although a single-institution study has suggested that alpha-defensin maintains its concentration and sensitivity even after antibiotic treatment, this has not yet been demonstrated in a larger multiinstitutional study.Questions/purposes(1) For the evaluation of PJI, is prior antibiotic admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 13 publications
2
48
1
8
Order By: Relevance
“…This result is in line with a study by Kasparek et al, who demonstrated a low sensitivity of 67% [17]. In one case (see Supplementary Table S1, knee 37) with a 'culture-negative PJI', the a-defensin result switched from positive preoperatively to negative intraoperatively after 2 days of antibiotic treatment, even though a previous antibiotic treatment has not been considered a concern [12,18].…”
Section: Discussionsupporting
confidence: 87%
“…This result is in line with a study by Kasparek et al, who demonstrated a low sensitivity of 67% [17]. In one case (see Supplementary Table S1, knee 37) with a 'culture-negative PJI', the a-defensin result switched from positive preoperatively to negative intraoperatively after 2 days of antibiotic treatment, even though a previous antibiotic treatment has not been considered a concern [12,18].…”
Section: Discussionsupporting
confidence: 87%
“…Culture technique was improved by using blood culture bottles 49 , and longer duration of culture growth led to higher detection of P. acnes 50 . Over the past year, studies further evaluated other synovial fluid markers including procalcitonin, a-defensin, and leukocyte esterase [51][52][53][54][55] . The a-defensin lateral flow test introduced in Europe demonstrated findings similar to those of intraoperative frozen sections, with a sensitivity of 67% and a specificity of 93% 56 .…”
Section: Shoulder and Elbowmentioning
confidence: 99%
“…The authors concluded that if the alpha-defensin test is negative, then ''it is quite likely that the pain in the joint after THA or TKA is not caused by PJI.'' Previous studies [5][6][7]12] …”
Section: P Eriprosthetic Joint Infectionmentioning
confidence: 99%
“…A rapid molecular test that would provide the species of bacteria and drug sensitivity would be even better. Finally, the cell biology of alpha-defensin release, most likely from macrophages in some cases of metallosis, and the modulation of macrophage proinflammatory cytokine release by alpha defensins [12] are of interest with respect to the basic science of inflammation and the various adverse local tissue reactions associated with failed arthroplasty.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%